The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1177/1524838019865927
|View full text |Cite
|
Sign up to set email alerts
|

Compared to What? A Meta-Analysis of Batterer Intervention Studies Using Nontreated Controls or Comparisons

Abstract: This meta-analysis updates the literature on the effectiveness of batterer intervention programs (BIPs) in decreasing recidivism of domestic violence (DV) by focusing on studies with nontreated comparison groups ( N = 17). Included studies were published between 1986 and 2016, and 14 of the 17 provided sufficient information for the meta-analysis. Analysis focused on three reported outcomes: DV recidivism reported by the criminal justice system, intimate partner violence (IPV) perpetration assessed by the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 60 publications
2
70
0
Order By: Relevance
“…The first of the study's limitations concerns the use of official recidivism rates as the dependent variable. Because victims' reports of offender recidivism (compared to offender or official reports) tend to yield higher recidivism rates, relying on data from official reports underestimates the amount of actual recidivism (Cheng, Davis, Jonson-Reid, & Yaeger, 2019;Goldstein et al, 2016;Williams & Houghton, 2004). However, this was not possible in this study because Spanish legislation prevents the services referring IPVAW perpetrators to intervention programs from providing information that would allow access to their victims (Lila et al, 2018).…”
Section: Article In Pressmentioning
confidence: 90%
“…The first of the study's limitations concerns the use of official recidivism rates as the dependent variable. Because victims' reports of offender recidivism (compared to offender or official reports) tend to yield higher recidivism rates, relying on data from official reports underestimates the amount of actual recidivism (Cheng, Davis, Jonson-Reid, & Yaeger, 2019;Goldstein et al, 2016;Williams & Houghton, 2004). However, this was not possible in this study because Spanish legislation prevents the services referring IPVAW perpetrators to intervention programs from providing information that would allow access to their victims (Lila et al, 2018).…”
Section: Article In Pressmentioning
confidence: 90%
“…IPV offender intervention programs are one of the main treatment approaches aimed at preventing further violence (Cannon et al, 2016;Price & Rosenbaum, 2009;Voith et al, 2018). However, metaanalyses focused on the effectiveness of IPV offender intervention programs have shown small effect sizes (Arias et al, 2013;Babcock et al, 2004;Cheng et al, 2019;Eckhardt et al, 2013;Feder & Wilson, 2005;Gondolf, 2004;Smedslund et al, 2011).…”
Section: Las Estrategias Motivacionales En Las Intervenciones Con Agrmentioning
confidence: 99%
“…Several meta-analyses conducted to evaluate the effectiveness of batterer intervention programs (BIPs) have indicated that the effect size of these interventions on reducing recidivism tends to be small (Arce et al, 2020;Babcock et al, 2004;Cheng et al, 2019;Eckhardt et al, 2013;Feder & Wilson, 2005;Smedslund et al, 2011). This limited success of BIPs in reducing recidivism has been attributed to different factors such as low treatment compliance and high dropout rates (Bennett et al, 2007;Daly & Pelowski, 2000;Jewell & Wormith, 2010;Lila et al, 2019;Olver et al, 2011), lack of motivation for change Crane et al, 2015;Eckhardt et al, 2008;Zalmanowitz et al, 2013), problems in building the working alliance (Cadsky et al, 1996;DiGiuseppe et al, 1994;Murphy & Baxter, 1997;Taft et al, 2004), and poor engagement in program activities (Musser et al, 2008;Taft et al, 2003).…”
mentioning
confidence: 99%